APHA thin ewe investigation project. (6th August 2021) - Bell, Suzi; Carson, Amanda; Collins, Rachael; Dunnett, Lizzy; Reichel, Rudolf; Richey, Moyna
Abstract : This focus article has been prepared by Suzi Bell, Amanda Carson, Rachael Collins, Lizzy Dunnett, Rudolf Reichel and Moyna Richey of the APHA Small Ruminant Expert Group.